Mama [videorecording (DVD)] - Muschietti, Andrés; Cross, Neil; Chastain, Jessica, 1977-; Coster-Waldau, Nikolaj, 1970-; Charpentier, Megan, 2001- (Universal Studios Home Entertainment, 2013)
A supernatural thriller that tells the haunting tale of two little girls who disappeared into the woods the day that their parents were killed. When they are rescued years later and begin a new life, they find that someone or something still wants to come tuck them in at night.